A New Case of DRESS Syndrome Induced by Sulfasalazine and Triggered by Amoxicillin - Francesco Girelli; Simone Bernardi; Lucia Gardelli; Bruna Bassi; Gianluca Parente; Alessandra Dubini; Luigi Serra; Maurizio Nizzoli (Case Reports in Rheumatology)
Drug Rash Eosinophilia Systemic Symptoms (DRESS) syndrome is a systemic hypersensitivity reaction characterized by exfoliative dermatitis and maculopapular rash, lymphadenopathy, fever, eosinophilia, leukocytosis, and involvement of internal organs as liver, lung, heart, and kidney; the disorder starts within 2–6 weeks after taking a drug with an incidence that ranges from 1/1000 to 1/10000 exposures. Fatal cases are reported. The exact pathogenesis of DRESS syndrome is not completely understood, while it is reported that amoxicillin could trigger it in patients who are taking allopurinol, sulfasalazine, NSAIDs, carbamazepine, strontium ranelate, lisinopril, lansoprazole, and minocycline. Amoxicillin could act directly, inducing the reactivation of a viral infection (HHV 6 and EBV) with symptoms similar to DRESS syndrome or by reducing the patients’ ability to detoxify the body from substances chronically taken. We describe a case of a patient admitted to our hospital for a DRESS syndrome flared after amoxicilline intake during treatment with sulfasalazine; this combination can activate severe reactions often with an insidious onset that can mimic an infectious disease.